Decision Support System for Muhammadiyah Pekuncen Islamic Junior High School in Determining Excellent Students Using the AHP Method - Rahma, Felinda Aprilia; Diniyati, Faoziyah Fahiya; Hidayah, Septi Oktaviani Nur; Tahyudin, Imam (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2022)
MTs Muhammadiyah Pekuncen is one of the MTs in the Banyumas Regency area where each year determines superior students and gets a 50% tuition discount for these students, with the aim of motivating students to become even better. Excellent students are students with high achievement, noble character and good behavior. Determination of superior students at MTs Muhammadiyah Pekuncen is still done manually, namely by deliberation between the teacher council which results in differences of opinion. Therefore we need a system that can determine superior students fairly without taking sides with any party and can be accepted by teachers and students. In this study, it will produce data on students who are selected to be superior students with 5 criteria including attitude, attendance, social, activity and achievement based on the AHP algorithm process. With the existence of a Decision Support System using the Analytical Hierarchy Process method it is proven to produce accurate values in determining superior students at Mts Muhammadiyah Pekuncen with a total value of 0.4464 a class IX student named Seftria Salsabila Putri was selected as a superior student.